2022
DOI: 10.3390/jcdd9100345
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Severity in Ischemic Stroke Patients with a History of Diastolic Blood Pressure Treated in a Telestroke Network

Abstract: Background: The relationship between diastolic blood pressure (DBP), risk factors, and stroke severity in acute ischemic stroke (AIS) patients treated in a telestroke network is not fully understood. The present study aims to determine the effect of risk factors on stroke severity in AIS patients with a history of elevated DBP. Material and Methods: We retrospectively analyzed data on stroke severity for AIS patients treated between January 2014 and June 2016 treated in the PRISMA Health telestroke network. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…This did not reveal any statical significant differences between hypertension and stroke severity (p=0.48), that was similarly reported by Sivaji et al from India [21] and Omar et al from Sudan [23]. However, hypertension had a significant association with stroke severity in several studies [41,42], which could be explained by the fact that the reason for this discrepancy may be related to small sample size.…”
Section: Discussionsupporting
confidence: 48%
“…This did not reveal any statical significant differences between hypertension and stroke severity (p=0.48), that was similarly reported by Sivaji et al from India [21] and Omar et al from Sudan [23]. However, hypertension had a significant association with stroke severity in several studies [41,42], which could be explained by the fact that the reason for this discrepancy may be related to small sample size.…”
Section: Discussionsupporting
confidence: 48%
“…20 Other studies, however, have found that diastolic blood pressure more than 80 mmHg is associated with poor outcomes in cases of ischemic stroke. 35,36 The majority of the study subjects (n = 32, n% = 80%) had systolic blood pressure > 140 mmHg or diastolic blood pressure > 90 mmHg when they arrived at the hospital. With these values, blood pressure can be categorized as stage 2 hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, obese individuals who are smokers present with a risk of circulatory and cerebrovascular diseases with increased mortality by 7- to 10-fold for smokers compared to normal-weight and non-smokers [ 9 ]. Both smoking and obesity have been linked to increased incidence of stroke in both male and female AIS patients [ 10 , 11 ], but sex differences in obese AIS patients with a current or previous history of smoking are not fully understood.…”
Section: Introductionmentioning
confidence: 99%